1992
DOI: 10.1079/bjn19920074
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a fish oil high in docosahexaenoic acid on plasma lipoprotein and vitamin E concentrations and haemostatic function in healthy male volunteers

Abstract: Nine healthy male subjects consumed a daily fish oil supplement providing 2.1 g docosahexaenoic acid (22:6 n-3; DHA) and 0 8 g eicosapentaenoic acid (20:5 n-3; EPA) for 6 weeks. The proportion of EPA and DHA in plasma, erythrocytes, leucocytes and platelet phospholipids was increased by the supplement. Plasma concentration of triacylglycerol and very-low-density-lipoprotein-cholesterol were lowered and those of high-density-lipotrotein (HDL)-and HDL,-cholesterol and apoprotein B were increased. Platelet aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
26
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 31 publications
7
26
0
Order By: Relevance
“…A small but statistically significant fall in packed cell volume has also been noted in some studies using fish oil supplements (Sanders & Hinds, 1992) and in a study where the subjects consumed fish paste (Van Houwelingen et al 1987).…”
Section: Interaction With Antioxidant Nutrientsmentioning
confidence: 96%
See 1 more Smart Citation
“…A small but statistically significant fall in packed cell volume has also been noted in some studies using fish oil supplements (Sanders & Hinds, 1992) and in a study where the subjects consumed fish paste (Van Houwelingen et al 1987).…”
Section: Interaction With Antioxidant Nutrientsmentioning
confidence: 96%
“…Several studies have noted falls in plasma vitamin E concentrations following fish oil supplementation (Bjorneboe et al 1988;Sanders & Hinds, 1992); this may occur even though additional vitamin E and antioxidants are added to the oil. A small but statistically significant fall in packed cell volume has also been noted in some studies using fish oil supplements (Sanders & Hinds, 1992) and in a study where the subjects consumed fish paste (Van Houwelingen et al 1987).…”
Section: Interaction With Antioxidant Nutrientsmentioning
confidence: 99%
“…The effects of fi sh oil or n-3 polyunsaturated fatty acids on blood coagulation and fi brinolysis have been examined [6][7][8] and several studies have found that fi sh oil containing eicosapentaenoic acid (EPA) reduced platelet aggregability [9,10] . However, the effects of dietary fi sh oil on blood coagulation and fi brinolysis and their mechanisms have been controversial.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] In certain situations such as heavy exercise, 8 high purified o3 highly unsaturated fatty acids intakes, 10,11,13 insufficient antioxidant cover 8,9 and significant pre-existing oxidative stress and/or inflammatory pathology, 8,13 this may create a pro-inflammatory environment, manifesting inter alia with increased DNA damage 9 and increased levels of soluble vascular cell adhesion molecule (sVCAM-1). 13 It is important to point out that others have found sVCAM-1 to be reduced; 15 the divergent findings may reflect different intakes of dietary ancillary factors in different populations.…”
Section: Too Pure To Be True?mentioning
confidence: 99%